2000
DOI: 10.1007/s002230010024
|View full text |Cite|
|
Sign up to set email alerts
|

Bone Mineral Densitometry Substantially Influences Health-Related Behaviors of Postmenopausal Women

Abstract: Although bone mineral density measurements are helpful in predicting future risk for osteoporotic fractures, there is limited information available on how the results of bone densitometry influence a woman's use of therapeutic alternatives. To assess the role of bone mineral densitometry in influencing postmenopausal women to change health behaviors associated with osteoporosis, we prospectively followed, for an average of 2.9 years, 701 postmenopausal women over 50 years of age referred to an osteoporosis pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
(26 reference statements)
3
31
1
Order By: Relevance
“…Age was not associated with women making a change in calcium intake after osteoporosis screening. Marci et al (13) also found that age, education, and history of osteoporosis, were not associated with starting calcium supplements. In addition, Rubin and Cummings (11) found that education was not associated with behavioral changes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Age was not associated with women making a change in calcium intake after osteoporosis screening. Marci et al (13) also found that age, education, and history of osteoporosis, were not associated with starting calcium supplements. In addition, Rubin and Cummings (11) found that education was not associated with behavioral changes.…”
Section: Discussionmentioning
confidence: 94%
“…They found that women with below-normal BMD were 3 times as likely to start or increase calcium supplementation and increase their consumption of milk or calcium-rich food. Marci et al (13) found that BMD results were the most significant predictor of changes in calcium intake, and, in a recent study by Rohr et al (14), there was a significant increase in calcium-supplement intake in postmenopausal women with low BMD. Other studies report an increase in calcium intake after screening; however, these studies had a limited baseline evaluation and therefore no assessment of change (20)(21)(22), they did not use DXA the gold standard for BMD measurement (20,23), and they had a study population that included premenopausal women (20,22,12).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings that initiation of estrogen is highest among women with lowest bone density. 18,19 We believe that the ultrasound with feedback of fracture risk was a critical part of this intervention, especially for individuals with lower BMD 20 because at baseline, there was low levels of concern and knowledge about osteoporosis. Low levels of understanding regarding osteoporosis has been shown previously.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up survey showed that 70% of respondents discussed the results with their physicians and that some women began taking calcium, multivitamins, vitamin D, or antiresorptive therapy. Related studies [47][48][49] have shown that women receiving central DXA measurements were more adherent with therapy and lifestyle changes than women who were not tested. The current work demonstrates that when the results of BMD screening are provided to the patient and/or physician, appropriate and potentially beneficial interventions can result.…”
Section: Discussionmentioning
confidence: 99%